Cell rupture of recombinant escherichia coli using high pressure homogenizer - Ahmad Raus, Raha; Mel, Maizirwan; Mohd Abdullah, S. N.; Yusoff, K. (Asian Network for Scientific Information, 2010)
Cell rupture is one of the earlier steps in downstream processing which are required for the recovery of biological products that are located inside cells. Cells could be disrupted either by using chemicals or mechanical method. In this study, cell rupture was carried out by mechanical force using High Pressure Homogenizer (HPH). The aim of this study is to identify optimal conditions of HPH to disrupt the cell wall of recombinant Escherichia coli harboring nucleocapsid (NP) gene of Newcastle Disease Virus (NDV). The optimized conditions were achieved by manipulating the independent variables of HPH such as pressure, pump speed and number of cycles through an optimization process. The efficiency of the cell disruption was determined by estimating the percentage of cell rupture as well as the amount of NP protein released from the cell lysis. Through the means plot analysis of Minitab Software (Version 14.12), pressure was recognized as the main factor for achieving the highest cell rupture and the release of NP protein. The optimized conditions for obtaining the highest NP protein yield were by operating three cycles of cell rupture, homogenizer pressure of 800 bars and pump speed of 7 psi.